An overview of the TROPICS NASA Earth Venture Mission. (17th September 2018) - Blackwell, W. J.; Braun, S.; Bennartz, R.; Velden, C.; DeMaria, M.; Atlas, R.; Dunion, J.; Marks, F.; Rogers, R.; Annane, B.; Leslie, R. V.
Abstract : The Time‐Resolved Observations of Precipitation structure and storm Intensity with a Constellation of Smallsats (TROPICS) mission was selected by NASA as part of the Earth Venture‐Instrument (EVI‐3) program. The overarching goal for TROPICS is to provide nearly all‐weather observations of 3D temperature and humidity, as well as cloud ice and precipitation horizontal structure, at high temporal resolution to conduct high‐value science investigations of tropical cyclones. TROPICS will provide rapid‐refresh microwave measurements (median refresh rate better than 60 min for the baseline mission) which can be used to observe the thermodynamics of the troposphere and precipitation structure for storm systems at the mesoscale and synoptic scale over the entire storm life cycle. TROPICS comprises six CubeSats in three low‐Earth orbital planes. Each CubeSat will host a high‐performance radiometer to provide temperature profiles using seven channels near the 118.75 GHz oxygen absorption line, water vapour profiles using three channels near the 183 GHz water vapour absorption line, imagery in a single channel near 90 GHz for precipitation measurements (when combined with higher‐resolution water vapour channels), and a single channel near 205 GHz which is more sensitive to precipitation‐sized ice particles. This observing system offers an unprecedented combination of horizontal and temporal resolution to measure environmental and inner‐core conditions for tropical cyclones on a nearly global scale and is a major leap forward in the temporal resolution of several key parameters needed for assimilation into advanced data assimilation systems capable of utilizing rapid‐update radiance or retrieval data. Launch readiness is currently projected for late 2019. Abstract : Azimuth versus time plots of simulated 114.85 GHz brightness temperatures from a WRF nature run, averaged over a circle extending from the simulated TC centre to 120 km radius, and sampled at the indicated time intervals (a) 39 min, (b) 1, (c) 2, (d) 3, and (e) 6 hr. Lower temperatures correspond to the movement of convective bursts (CBs) around the eyewall (black arrows). There is good tracking of individual CBs for sampling intervals ≤1 h; tracking rapidly degrades for sampling intervals >2 h. The cluster of CBs between days 3 and 4 is associated with a rapid change of storm intensity during that time, as indicated by (f) the simulated minimum sea‐level pressure.